2019
DOI: 10.1108/ict-11-2018-0094
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the potential of human capital development to predict commitment: an empirical approach

Abstract: Purpose The purpose of this paper is to revisit the potential of human capital development to predict commitment from an empirical perspective. This followed the fact that while organisations continue to invest a lot of resources into development of their human capital, a growing tendency of the trained staff to quickly abandon the organisation and move on to search for greener pastures has also been registered. Design/methodology/approach This study takes a positivistic approach. It is an explanatory, cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…As revealed in the outcome of the analysis in Table 3, the first null hypothesis found out that human capital development does not significantly affect organisational commitment. This finding contradicts with the findings in the study of Muhumuza and Nangoli (2019) in the study of Uganda's healthcare sector that explore the relationship between human capital development and employee commitment. The research demonstrated that the improvement of human resources enhances staff commitment.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…As revealed in the outcome of the analysis in Table 3, the first null hypothesis found out that human capital development does not significantly affect organisational commitment. This finding contradicts with the findings in the study of Muhumuza and Nangoli (2019) in the study of Uganda's healthcare sector that explore the relationship between human capital development and employee commitment. The research demonstrated that the improvement of human resources enhances staff commitment.…”
Section: Resultscontrasting
confidence: 99%
“…Empirical studies have also revealed the connection between human development and organisational outcomes including commitment. Muhumuza and Nangoli (2019) in their study on how human capital development affects staff commitment in Uganda based on a crosssectional design, regression and correlation analysis of 52 responses obtained through questionnaire administration to the respondents in Mayanja Memorial Hospital in Uganda revealed that employees' commitment is enhanced by human capital development. Similarly, Opeke and Mayowa-Adebara (2020) in their study on how employee commitment is influenced by human capital development in South-West Nigeria University libraries based on survey design and regression analysis of responses obtained from 684 librarians in 43 universities through a questionnaire found that employee commitment is significantly influenced by human capital development.…”
Section: Human Capital Development and Organisational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge managers are encountering when implementing mechanisms for enhancing commitment is that the feasibility of strategies varies with time, indicating the need to regularly craft and pursue strategies that fit with the prevailing organisational environment (Enache et al , 2013). Past trends show that existing mechanisms are gradually losing their strategic fit and must be replaced with new, more efficient means of promoting commitment (Coetzer et al , 2017; Muhumuza and Nangoli, 2019). For example, while there has been a general reliance recently among marketing organisations on economic rewards for their employees, the need for an enhanced non-financial approach to staff commitment continues to resonate following the intensifying pressures on financial resources (Munga and Mbilinyi, 2008; Camilleri, 2017).…”
Section: Introductionmentioning
confidence: 99%